Characterization of the cutaneous mycobiota in healthy and allergic cats using next generation sequencing. Issue 1 (23rd August 2016) - Meason‐Smith, Courtney; Diesel, Alison; Patterson, Adam P.; Older, Caitlin E.; Johnson, Timothy J.; Mansell, Joanne M.; Suchodolski, Jan S.; Rodrigues Hoffmann, Aline
Abstract : Background: Next generation sequencing (NGS) studies have demonstrated a diverse skin‐associated microbiota and microbial dysbiosis associated with atopic dermatitis in people and in dogs. The skin of cats has yet to be investigated using NGS techniques. Hypothesis/Objectives: We hypothesized that the fungal microbiota of healthy feline skin would be similar to that of dogs, with a predominance of environmental fungi, and that fungal dysbiosis would be present on the skin of allergic cats. Animals: Eleven healthy cats and nine cats diagnosed with one or more cutaneous hypersensitivity disorders, including flea bite, food‐induced and nonflea nonfood‐induced hypersensitivity. Methods: Healthy cats were sampled at twelve body sites and allergic cats at six sites. DNA was isolated and Illumina sequencing was performed targeting the internal transcribed spacer region of fungi. Sequences were processed using the bioinformatics software QIIME. Results: The most abundant fungal sequences from the skin of all cats were classified as Cladosporium and Alternaria . The mucosal sites, including nostril, conjunctiva and reproductive tracts, had the fewest number of fungi, whereas the pre‐aural space had the most. Allergic feline skin had significantly greater amounts of Agaricomycetes and Sordariomycetes, and significantly less Epicoccum compared to healthy feline skin. Conclusions: The skin of healthy cats appears to have a more diverse fungal microbiota compared to previous studies, and a fungal dysbiosis is noted in the skin of allergic cats. Future studies assessing the temporal stability of the skin microbiota in cats will be useful in determining whether the microbiota sequenced using NGS are colonizers or transient microbes. Abstract : Background – Next generation sequencing (NGS) studies have demonstrated a diverse skin‐associated microbiota and microbial dysbiosis associated with atopic dermatitis in people and in dogs. The skin of cats has yet to be investigated using NGS techniques.Hypothesis/Objectives – We hypothesized that the fungal microbiota of healthy feline skin would be similar to that of dogs, with a predominance of environmental fungi, and that fungal dysbiosis would be present on the skin of allergic cats.Conclusions – The skin of healthy cats appears to have a more diverse fungal microbiota compared to previous studies, and a fungal dysbiosis is noted in the skin of allergic cats. Future studies assessing the temporal stability of the skin microbiota in cats will be useful in determining whether the microbiota sequenced using NGS are colonizers or transient microbes.